2024
DOI: 10.59158/001c.94532
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Counselling Profession in 2030: An Educator’s Perspective

Nathan Beel

Abstract: This paper explores the current and future status of the counselling profession in Australia. It reviews the progress and challenges of the profession in terms of recognition, regulation, training, and research. Envisioning a successful future, it attempts to describe that future and how the profession succeeded in accomplishing its goal of full recognition. The paper aims to stimulate ideas and discussions among counsellors and stakeholders to achieve a unified, consistent, and recognised profession that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…
Whether psychotherapy should be recognised as a specialist identity within the counselling profession (Beel, 2024) or as a separate profession in its own right (Gale, 2024) are questions raised in this issue's two Viewpoints articles. Another article, "The Movements of Grief" (Cox & Fenwick, 2024), draws on contemporary grief models to posit three phases of grief: transience, transition, and transformation, with a liminal space opening up during transition.
…”
mentioning
confidence: 99%
“…
Whether psychotherapy should be recognised as a specialist identity within the counselling profession (Beel, 2024) or as a separate profession in its own right (Gale, 2024) are questions raised in this issue's two Viewpoints articles. Another article, "The Movements of Grief" (Cox & Fenwick, 2024), draws on contemporary grief models to posit three phases of grief: transience, transition, and transformation, with a liminal space opening up during transition.
…”
mentioning
confidence: 99%
“…Valid concerns exist about practitioners, especially those in positions of power (such as in psychotherapy and counselling associations and counselling and psychotherapy educational roles), lacking proper training in psychotherapy, advocating for its conflation and, on occasion, its elimination. In the article "The Australian Counselling Profession in 2030: An Educator's Perspective", Nathan Beel (2024) suggested that being a psychotherapist should be a secondary identity to counselling. Furthermore, he recommended that the term psychotherapy be removed altogether from the title of the Psychotherapy and Counselling Federation of Australia (PACFA) and that the federation be rebranded as the Counselling Federation of Australia.…”
mentioning
confidence: 99%